Social determinants of health among residential areas with a high tuberculosis incidence in a remote Inuit community. Issue 5 (6th February 2019) - Kilabuk, Elaine; Momoli, Franco; Mallick, Ranjeeta; Van Dyk, Deborah; Pease, Christopher; Zwerling, Alice; Potvin, Sharon Edmunds; Alvarez, Gonzalo G
Abstract : Background: Tuberculosis (TB) remains a significant health burden among Inuit in Canada. Social determinants of health (SDH) play a key role in TB infection, disease and ongoing transmission in this population. The objective of this research was to estimate the prevalence of social determinants of Inuit health as they relate to latent TB infection (LTBI) among people living in residential areas at high risk for TB in Iqaluit, Nunavut. Methods: Inperson home surveys were conducted among those who lived in predetermined residential areas at high risk for TB identified in a door-to-door TB prevention campaign in Iqaluit, Nunavut in 2011. Risk ratios for SDH and LTBI were estimated, and multiple imputation was used to address missing data. Results: 261 participants completed the questionnaire. Most participants identified as Inuit (82%). Unadjusted risk ratios demonstrated that age, education, smoking tobacco, crowded housing conditions and Inuit ethnicity were associated with LTBI. After adjusting for other SDH, multivariable analysis showed an association between LTBI with increasing age (relative risk, RR 1.07, 95% CI 1.04 to 1.11), crowded housing (RR 1.48, 95% CI 1.10 to 2.00) and ethnicity (RR 2.76, 95% CI 1.33 to 5.73) after imputing missing data. Conclusion: Among high-risk residential areas for TB in a remote Arctic region of Canada, crowded housing and Inuit ethnicity were associated with LTBI after adjusting for other SDH. In addition to strong screening and treatment programmes, alleviating the chronic housing shortage will be a key element in the elimination of TB in the Canadian Inuit Nunangat.